Enhancing agency for health providers and pregnant women experiencing intimate partner violence in South Africa. Issue 12 (1st December 2020) - Sprague, Courtenay; Woollett, Nataly; Hatcher, Abigail M.
ABSTRACT: Global policy frameworks call for strengthening the role of health systems to address intimate partner violence (IPV) and support women's agency, yet the evidence of health system responses remains slender in low- and middle-income countries (LMICs). In South Africa, 25–35% of pregnant women experience IPV, posing long-term health risks. We utilised agency as a theoretical construct, applying qualitative methods to investigate health professionals' experiences of a randomised controlled trial intervention to address IPV in pregnant women in five antenatal clinics (ANC) in Johannesburg (2011–2016). In-depth interviews ( n = 16) were supplemented by participant observation, debriefing and field notes. Health providers viewed the intervention as enhancing health promotion agency and advancing help-seeking agency for IPV-exposed patients. Intervention nurses reported their own self-efficacy improved, and their relational and collective agency expanded . On-going supervision, mentorship and feedback were essential to establish the knowledge and skill-building necessary for providers to improve self-efficacy in intervention delivery. Integrating mental health services into primary ANC services is recommended. Findings offer insight into the untapped potential for LMIC health settings to become transformative, gender-responsive social systems, for patients and health professionals, in ways that advance women's agency, health, human rights and SDGs.